2023
DOI: 10.1093/genetics/iyad028
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of CENP-A/Cse4 on arginine 143 and lysine 131 regulates kinetochore stability in yeast

Abstract: Posttranslational modifications on histones are well known to regulate chromatin structure and function, but much less information is available on modifications of the centromeric histone H3 variant and their effect at the kinetochore. Here, we report two modifications on the centromeric histone H3 variant CENP-A/Cse4 in the yeast Saccharomyces cerevisiae, methylation at arginine 143 (R143me) and lysine 131 (K131me), that affect centromere stability and kinetochore function. Both R143me and K131me lie in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 57 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…A recent study has identified methylation within the C-terminus of Cse4 (K131 and R143), which affects the stability of CEN nucleosomes in the context of defects in outer kinetochore proteins, such as those of the Ndc80 complex ( Nguyen et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study has identified methylation within the C-terminus of Cse4 (K131 and R143), which affects the stability of CEN nucleosomes in the context of defects in outer kinetochore proteins, such as those of the Ndc80 complex ( Nguyen et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2019 ). The lack of any detectable phenotype in cse4-R37A could be due to compensatory effect produced by the methylation of R143 in the C-terminus of Cse4 ( Nguyen et al. , 2023 ) or other methylated arginine residues in Cse4 that are yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations